A New Probabilistic Output Constrained Optimization Extreme Learning Machine - Wong S.Y.; Yap K.S.; Li X.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Benchmarking; Classification (of information); Constrained optimization; Decision making; Electric power systems; Iterative methods; Knowledge acquisition; Learning algorithms; Pattern recognition; Probability; Confidence threshold; Decision making process; Extreme learning machine; Machine learning approaches; Pattern classification problems; Post-processing procedure; Power system applications; Probabilistic output; Machine learning